Segment-based resilience response and intervention evaluation of water distribution systems - Liu, Jun; Kang, Yinyin (Aqua (London, England), 2022)
The consideration of isolation valves and segments is essential for evaluating the water service and resilience of water distribution systems when shutdowns are required under pipe failure. However, little work has been done on assessing the resilience response and intervention based on segments. This study investigates the impact of intervention (valve density and protection of critical segment) and response (recovery time and recovery sequence) on system resilience taking valve layout into consideration. An algorithm to identify segments based on the graph theory is proposed. Resilience is quantified using the satisfactory rate of the water supply demand. Critical segments are ranked based on resilience analysis. The resilience evaluation method is applied to a case study network. It is found that valve optimization can significantly reduce the number of valves without considerably decreasing the resilience performance. Valve density and the protection of critical segment can reduce the severity of pipe failure, while efficient recovery response can reduce the severity and shorten the duration of pipe failure simultaneously. The criticality of segments depends on the segment location and hydraulic interdependency among segments.